Collective action for tackling "wicked" social problems: A system dynamics model for corporate community involvement. (1st April 2018) - Gold, Stefan; Muthuri, Judy N.; Reiner, Gerald
Abstract: Although corporations have been often accused of exacerbating social and environmental conditions in developing world regions where they operate, there are companies that sincerely engage in community development initiatives and aim for the delivery of public goods in poor regions. Still there is disquiet on how these companies go about undertaking community development initiatives spawning various forms of criticisms regarding negative side-effects of corporate social action. By means of system dynamics, and based on the longitudinal case study of Tata Chemicals Magadi (Kenya), this paper develops a model of collective action for development. Thereby it sheds light on the variables and mechanisms that are crucial for making community involvement projects an overall success for all actors involved while benefitting the initiating company. The model highlights in particular the importance of "we-feeling" between all relevant stakeholders and of participatory community development capacity. The results indicate that collaborative networks actively including local communities may foster communities' self-help capacity, while creating a positive feed-back loop to company performance. This study allows exploring new forms of social responsibility that leave behind corporate-focussed models for the sake of inclusive and participatory forms of shared responsibility, which is of relevance on both the academic and practical side, and may also be transferred to an industrialized world context. Highlights: 'Wicked' social problems such as poverty are complex and multi-dimensional. Corporations redefine their role and strategy in tackling 'wicked' social problems. Empirical case study of Tata Chemicals Magadi (Kenya) informs modelling approach. A system dynamics model of collective action for development is developed. New form of participatory and shared (corporate) social responsibility is explored.